The Utilization of Cajuput Leaf Waste as Organic Fertilizer on Plant Tomatoes Growth and Development - Widiana, Ana; Ukit, Ukit; Sudrajat, Azat (Al-Kauniyah: Jurnal Biologi, 2025)
AbstractThe annual production of cajuput oil in Indonesia can reach 88,607 tons. This has implications on the accumulation of the waste. One of the efforts to reduce the amount of cajuput waste is to use this waste as organic fertilizer. This study aimed to determine the content of C, N, P, and K of cajuput leaf waste fertilizer and their effect on the growth and development of tomato plants (Lycopersicum esculentum L.). This study used a Completely Randomized Design (CRD) with P0+ treatment (EM4 fertilizer); P0- (no fertilizer); and treatment with the ratio (%) of cajuput leaf waste fertilizer: chicken manure, including P1 (100:0); P2 (75:25); P3(50:50); P4 (25:75); P5(0:100). The results showed that P2 treatment had a higher content of N-total (2.82%) and C-Organic (44.28%) with a C/N ratio of 15.70%, directly proportional to the results of the best vegetative growth response, indicated by a plant height of 125.75 cm, stem diameter 0.665 cm, and the 15.75 number of leaves. The P2 treatment was considered to have the best for tomato plant development by producing fruit sizes (diameter; length) up to 3.40 cm; 3.49 cm with a weight of 20 g.AbstrakProduksi tahunan minyak kayu putih di Indonesia bisa mencapai 88.607 ton. Hal ini berimplikasi pada penumpukan sampah. Salah satu upaya untuk mengurangi jumlah limbah daun kayu putih adalah dengan memanfaatkan limbah tersebut sebagai pupuk organik. Penelitian ini bertujuan untuk mengetahui kandungan C, N, P, dan K pupuk limbah daun kayu putih serta pengaruhnya terhadap pertumbuhan dan perkembangan tanaman tomat (Lycopersicum esculentum L.). Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) Perlakuan P0+ (pupuk EM4); P0- (tanpa pupuk); dan perlakuan dengan perbandingan (%) pupuk limbah daun kayu putih dengan kotoran ayam, di antaranya P1 (100:0); P2 (75:25); P3 (50:50); P4 (25:75); P5 (0:100). Hasil penelitian menunjukkan bahwa perlakuan P2 memiliki kandungan N-total (2,82%) dan C-Organik (44,28%) yang lebih tinggi dengan rasio C/N 15,70%, berbanding lurus dengan hasil respon pertumbuhan vegetatif terbaik yang ditunjukkan oleh tinggi tanaman 125,75 cm, diameter batang 0,665 cm dan jumlah daun 15,75. Perlakuan P2 dinilai paling baik untuk perkembangan tanaman tomat dengan menghasilkan ukuran buah (diameter; panjang) hingga 3,40 cm; 3,49 cm dengan berat 20 g.